My hero academia smash!! 3 - Neda, Hirofumi; Cook, Caleb D.; Horikoshi, Kōhei, 1986-; Neda, Hirofumi (San Francisco, CA : VIZ Media, LLC, 2020)
"This volume of the My Hero Academia parody series treats hero education like a joke! First, the aspiring heroes of U.A. High enjoy fun in the sun on their summer break. Then, exams are replaced by silly student vs. teacher games assigned at random! Plus Izuku and company in their Halloween costumes and as animals! What are we teaching these kids?!"--Back cover.
"Original concept by Kohei Horikoshi."
Translation of: Boku no hiro akademia sumasshu.
Young Adult
Keywords: Ability -- Comic books, strips, etc. -- Fiction; Fantasy comic books, strips, etc; High schools -- Comic books, strips, etc. -- Fiction; Humorous stories; Superheroes -- Comic books, strips, etc. -- Fiction; Supervillains -- Comic books, strips, etc. -- Fiction; Ability -- Comic books, strips, etc. -- Fiction; Fantasy graphic novels; High schools -- Comic books, strips, etc. -- Fiction; Humorous graphic novels; Manga; Superhero graphic novels; Superheroes -- Comic books, strips, etc. -- Fiction; Supervillains -- Comic books, strips, etc. -- Fiction; Fantasy comics; Graphic novels; Humorous comics; Superhero comics